Comprensión lectora en los docentes de educación básica de la región Junín - Yarlequé, Luis (2012)
The investigation that turns up belongs to fellow once was applied and of descriptive level. The region's reader of the teachers of the 3 basic education levels studied understanding herself In her Junín. He used the descriptive method with a descriptive design comparative, one had a 357- subjects sign whom applied a compression test reader once was developed in order to the investigation's properties itself. Aftermaths permitted testing among other things that the basic education level whereon operates the teachers reader does not grant him perks or significant disadvantages in her understanding , likewise than the variables kind , labor situation , institution that I develop his professional studies in and enclosure the postgrade studies , they do not have a distinctive paper in the understanding the teachers's reader.